Is the Evaluation of Quality of Life in NSCLC Trials Important? Are the Results to be Trusted? - Hirsh, Vera (Frontiers in Oncology, 2014)
The majority of patients with non-small cell lung cancer (NSCLC) present at the time of diagnosis with stage IV metastatic disease and they experience 2 or more disease -related symptoms. These symptoms may have a negative impact on their health-related quality of life (HR QOL). Data has shown many of these patients prefer a therapy to improve their symptoms rather than receive a therapy which slightly prolongs their survival without improving their symptoms.The improvement of disease-related symptoms on a specific drug or regimen augments the significance of prolongation of the progression-free survival or the response rate as well as symptom worsening.The choice of the questionnaires to evaluate patients' reported outcomes (PROs) and HR QOL benefits and the methods of collecting the data and their interpretations are very important. Only if the data are collected and analyzed properly will they be meaningful and can then be viewed as components that add the total value to a treatment and provide a comprehensive picture of the benefits and risks of a certain anticancer therapy.